2013
DOI: 10.1002/cncr.27970
|View full text |Cite
|
Sign up to set email alerts
|

The impact of radiation therapy sequencing on survival and cardiopulmonary mortality in the combined modality treatment of patients with esophageal cancer

Abstract: BACKGROUND: The addition of chemoradiation (CRT) to surgery has been shown to improve survival in patients with esophageal cancer. In the current study, the authors determined whether the sequencing of CRT has an effect on survival and cardiopulmonary mortality in patients with esophageal cancer. METHODS: Patients with the following inclusion criteria were identified within 17 Surveillance, Epidemiology, and End Results registries from 1988 through 2007: adenocarcinoma or squamous cell carcinoma of the esophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…However, in our study, we conducted a thorough sensitivity analysis to assess the effects of unmeasured variables, such as clinical tumor staging. 2 A similar sensitivity analysis demonstrated that, even if the preoperative patients were half as likely to have comorbid disease as postoperative patients, our statistically significant results would hold.Palma et al suggest that some of the postoperative patients may have received radiotherapy for palliation of early recurrence after surgery, confounding the results. This is unlikely, because SEER data only capture first course of treatment information within 4 months of the cancer diagnosis, and the likelihood of patients developing recurrence within the first few months after surgery is less than 5% according to recent randomized data.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…However, in our study, we conducted a thorough sensitivity analysis to assess the effects of unmeasured variables, such as clinical tumor staging. 2 A similar sensitivity analysis demonstrated that, even if the preoperative patients were half as likely to have comorbid disease as postoperative patients, our statistically significant results would hold.Palma et al suggest that some of the postoperative patients may have received radiotherapy for palliation of early recurrence after surgery, confounding the results. This is unlikely, because SEER data only capture first course of treatment information within 4 months of the cancer diagnosis, and the likelihood of patients developing recurrence within the first few months after surgery is less than 5% according to recent randomized data.…”
mentioning
confidence: 51%
“…However, in our study, we conducted a thorough sensitivity analysis to assess the effects of unmeasured variables, such as clinical tumor staging. 2 A similar sensitivity analysis demonstrated that, even if the preoperative patients were half as likely to have comorbid disease as postoperative patients, our statistically significant results would hold.…”
mentioning
confidence: 51%
“…At presentation, more than one‐third of esophageal cancer patients have stage II or III disease . Multimodality treatments, including different combinations of radiotherapy and various chemotherapy regimens, may improve overall prognosis . Currently, preoperative chemoradiation followed by surgery is the most preferred treatment for stage II‐III thoracic esophageal squamous cell carcinoma (TESCC) of the middle or distal third .…”
Section: Introductionmentioning
confidence: 99%
“…various chemotherapy regimens, may improve overall prognosis. [4][5][6][7][8] Currently, preoperative chemoradiation followed by surgery is the most preferred treatment for stage II-III thoracic esophageal squamous cell carcinoma (TESCC) of the middle or distal third. [9][10][11] However, because of the pathological heterogeneity of patients enrolled in different studies, the survival benefit provided by preoperative chemoradiation has not yet been definitely established.…”
mentioning
confidence: 99%
“…We read with interest the recent study by Wojcieszynski and colleagues, who used the Surveillance, Epidemiology, and End Results (SEER) database to assess "whether the sequencing of chemoradiotherapy (CRT) has an effect on survival and cardiopulmonary mortality" for esophageal cancer. 1 Although chemotherapy data are not available in SEER, the authors use the delivery of radiotherapy (RT) as a surrogate for CRT, assuming that RT is "almost always administered concurrently with chemotherapy." 1 The findings are striking: the use of preoperative RT was associated with a 10% improvement in 5-year survival compared with postoperative RT (P < .0001).…”
mentioning
confidence: 99%